Analyzing YouTube Videos Shared on WhatsApp and Telegram Political Public Groups - Pereira, Érica Verônica; Melo, Philipe; Júnior, Manoel; Mafra, Vitor O.; Reis, Julio C. S.; Benevenuto, Fabrício (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2022)
As the use of smartphones in Brazil has advanced in recent years, instant messaging platforms such as WhatsApp and Telegram became part of Brazilians’ lives and communication. However, the use of these platforms is not limited to exchanging messages between two users but also serves as a platform for group discussions and content dissemination. This study focuses on YouTube videos shared by politically oriented public groups on WhatsApp and Telegram during the COVID -19 pandemic in Brazil. Specifically, we analyze the information disseminated by political groups about the pandemic and the main events that took place during the same period, highlighting the main differences between the platforms. Our investigation shows a relevant political bias in the content shared in public groups in Brazil, with predominantly right-oriented content in messaging apps. A significant overlap of popular videos between these platforms was also found. On YouTube, we found the main categories of videos and examined the narrative that these videos give us from the perspective of WhatsApp and Telegram users.